Feminist Impact via Chinese Social Media: A Post Content Analysis of Xiaohongshu - Changjian Geng; Hanif Abdurahman Siswanto; Kailai Zhang; Ming Hou; Qiaosheng Na; Mohammad Reevany Bustami (Jurnal Partisipatoris, 2024)
This paper discusses the impact of feminism on women through the Chinese social media and e-commerce platform—Xiaohongshu. Sentiment and themes were categorized for 50 top posts of feminism, which ranged from feminism Comment, female power education to analysis of movie and news. The research reveals that different content categories, emotional tones, and commentator feedback significantly influence user engagement. This study is also an indication of active engagement and diversity of ideas on issues of feminism by young Chinese women. These findings offer valuable insights for content creators and platform operators, emphasizing the need to consider emotional and categorical dynamics in strategy development to optimize user experience and content dissemination on Xiaohongshu.